2003
DOI: 10.1111/1539-6924.00346
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Environmental Hazards in Hong Kong Chinese

Abstract: A public sample of Hong Kong Chinese (N = 167) rated the levels of threat of 25 environmental hazards and gave quantitative judgments to six risk characteristics for each hazard. It was found that women, older participants, and less educated individuals found the hazards to be more threatening to the environment than did men, younger participants, and more educated individuals, respectively. A new spatial model emerged from a principal component analysis carried out on responses to six risk characteristics. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 19 publications
4
23
2
Order By: Relevance
“…This result is similar to that of Lai and Tao [24], who found that women were more concerned about environmental hazards than men. This is different compared to the study by Howel et al [25] who found no association with gender regarding perception of air pollution and health.…”
Section: Discussionsupporting
confidence: 90%
“…This result is similar to that of Lai and Tao [24], who found that women were more concerned about environmental hazards than men. This is different compared to the study by Howel et al [25] who found no association with gender regarding perception of air pollution and health.…”
Section: Discussionsupporting
confidence: 90%
“…But I would feel more confident about these observations if they were based on multiple studies with sample sizes of 250–400 in each racial/ethnic group instead of a typical random sample of 800–1,600 Americans where the sample sizes of the minority groups are 50–100 for each nonwhite group. Because the non-European population has grown so rapidly and will continue to do so, and because the literature shows that environmental concern is culturally dependent (Bronfman and Cifuentes 2003; Chuk-ling Lai and Tao 2003; Jianguang 1994; Karpowicz-Lazreg and Mullet 1993), I believe that we must not take support for environmental protection from rapidly increasing Asian American and Hispanic American populations for granted. Hence, I conducted a study to collect relatively equal numbers of non-Hispanic whites, non-Hispanic blacks, Asian, and Hispanic Americans in New Jersey to answer two questions: How comparatively concerned are non-Hispanic whites, non-Hispanic blacks, Asian Americans, and Hispanic Americans about environmental protection?…”
mentioning
confidence: 99%
“…The most obvious correlates are dread and grave consequences. ( 4–7,33–37 ) That is, if as expected, war/terrorism, lack of health care insurance, and drinking polluted water are at the top of the list of priorities, it is primarily because the public dreads them and personally fears the consequences of these risks. If, as expected, genetic engineering and climate change are not high priorities, it is because they are not dreaded and are perceived to have small consequences for people.…”
Section: Expectationsmentioning
confidence: 98%
“…Only 4 of the 106 papers were primarily about perceptions of risk‐related issues among non–Anglo‐Europeans. ( 4–7 ) There is almost no empirical research on the risk‐related judgments of non‐Western populations in the Anglo‐European studies because their impact is obscured in large national and regional random sample surveys. Johnson ( 1 ) observes that ethnic identity and acculturation might not be more important than psychometric measures, emotions, or other factors, but that they should be explored.…”
Section: Introductionmentioning
confidence: 99%